Osteoporosis and Dietary Factors - Ahmet Dinç; Merih Eryavuz (Galenos Yayinevi, 2002)
Among the determinants of osteoporosis in elderly, nutritional factors phlay a significant role. Various studies have found relationships between the level of dietary intake of different nutritients and calcium-phosphate or bone metabolism and come to the coclusion that either a deficient or an excessive nutritional intake could negatively affect the balance of calcium.